2022
DOI: 10.12659/msm.938826
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Activity-Dependent Plasticity and Persistent Enhancement of Synaptic Transmission in Alzheimer Disease: A Review of the Current Status

Abstract: Alzheimer disease (AD) is a chronic and heterogeneous neurodegenerative disorder characterized by complex pathological processes involving neuroinflammation, neurodegeneration, and synaptic dysfunction. Understanding the exact neurobiological mechanisms underlying AD pathology may help to provide a biomarker for early diagnosis or at least for assessment of vulnerability to dementia development. Neural plasticity is defined as a capability of the brain to respond to alterations including aging, injury, or lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 170 publications
0
5
0
Order By: Relevance
“…Recently, cerebrovascular dysfunction has emerged as an early manifestation of Alzheimer's disease with a direct impact on the evolution and clinical expression of dementia. It has been shown that mice expressing mutated tau exhibit a selective suppression of neural activity-induced CBF increases that precedes tau pathology and cognitive impairment (Warpechowski et al, 2023 ). Regarding stroke, these parametric maps help to diagnose and predict the final cerebral ischemic stroke volume identifying core and penumbra regions (Demeestere et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, cerebrovascular dysfunction has emerged as an early manifestation of Alzheimer's disease with a direct impact on the evolution and clinical expression of dementia. It has been shown that mice expressing mutated tau exhibit a selective suppression of neural activity-induced CBF increases that precedes tau pathology and cognitive impairment (Warpechowski et al, 2023 ). Regarding stroke, these parametric maps help to diagnose and predict the final cerebral ischemic stroke volume identifying core and penumbra regions (Demeestere et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to acquire functional information about perfusion-related parameters such as cerebral blood flow (CBF), mean transit time (MTT), and cerebral blood volume (CBV) (Keston et al, 2003 ; Østergaard, 2004 ). The accurate quantification of these parameters has several clinical applications, including the identification and evaluation of ischemic stroke prior to treatment (Calamante et al, 2002 ; Callewaert et al, 2021 ), the description of lesions associated with multiple sclerosis (Haselhorst et al, 2000 ; D'haeseleer et al, 2015 ), the diagnosis of tumors (Stadlbauer et al, 2015 ; Choi et al, 2016 ), or as trackers of Alzheimer's disease progression (Lacalle-Aurioles et al, 2014 ; Warpechowski et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…CSF biomarkers of plasticity include: neurogranin, a postsynaptic protein involved in synaptic plasticity and LTP [37], whose levels are usually higher in AD patients [38]; synaptosome-associated protein-25 (SNAP-25), which participates in the control of synaptic plasticity [39] and is usually higher in AD patients [40]; brain-derived neurotrophic factor (BDNF), essential for memory formation and structural plasticity [41] Measuring neuroplasticity in human subjects is obviously precluded by ethical and methodological considerations, calling for the use of proxy measures. Thus, measuring neuroplasticity was for many years restricted to the use of neuropsychological tests [30], such as the Battery of Learning Potential for Assessing Dementia [31] or the re-adapted Auditory Verbal Learning Test [32], and indirect biomarkers in serum and cerebrospinal fluid (CSF) [33][34][35][36]. CSF biomarkers of plasticity include: neurogranin, a postsynaptic protein involved in synaptic plasticity and LTP [37], whose levels are usually higher in AD patients [38]; synaptosome-associated protein-25 (SNAP-25), which participates in the control of synaptic plasticity [39] and is usually higher in AD patients [40]; brain-derived neurotrophic factor (BDNF), essential for memory formation and structural plasticity [41] and which is lower in MCI and AD patients [42,43]; and vascular endothelial growth factor (VEGF), a protein involved in the growth of blood vessels and delivery of glucose that has a role in enhancing neurogenesis and synaptic plasticity [33] (see Table 1).…”
Section: The Multiple Facets Of Neuroplasticitymentioning
confidence: 99%
“…Synaptic dysfunction is an early sign of AD ( Tönnies and Trushina, 2017 ). Long-term potentiation (LTP) and long-term depression (LTD) are crucial for regulating synaptic connections between neurons ( Warpechowski et al, 2023 ). LTP refers to the long-lasting increase in synaptic strength, while LTD is defined as the opposing process.…”
Section: Gsk-3β In Admentioning
confidence: 99%